2019
DOI: 10.1371/journal.pmed.1002903
|View full text |Cite
|
Sign up to set email alerts
|

Estimated stroke risk, yield, and number needed to screen for atrial fibrillation detected through single time screening: a multicountry patient-level meta-analysis of 141,220 screened individuals

Abstract: BackgroundThe precise age distribution and calculated stroke risk of screen-detected atrial fibrillation (AF) is not known. Therefore, it is not possible to determine the number needed to screen (NNS) to identify one treatable new AF case (NNS-Rx) (i.e., Class-1 oral anticoagulation [OAC] treatment recommendation) in each age stratum. If the NNS-Rx is known for each age stratum, precise cost-effectiveness and sensitivity simulations can be performed based on the age distribution of the population/region to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
84
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 44 publications
7
84
1
3
Order By: Relevance
“…New to the field, our study demonstrated the strong association between positive AF screening and HD diagnosed by echo, besides the known increasing prevalence with age. This aligns with a meta-analysis of 19 studies (14 in low-income to middle-income and high-income countries) with 141 220 participants showing that AF rates increased from 0.34% (<60 years) to 2.73% (≥85 years) and that screen-positive patients are at elevated risk of stroke, with the majority of individuals >65 years having indication of anticoagulation for stroke prevention and >70% having at least one additional stroke risk factor 27. Additionally, some studies postulate that, more than a marker of CV involvement, AF may be an HD itself, being an independent predictor of structural damage and clinical outcomes 28 29.…”
Section: Discussionsupporting
confidence: 79%
“…New to the field, our study demonstrated the strong association between positive AF screening and HD diagnosed by echo, besides the known increasing prevalence with age. This aligns with a meta-analysis of 19 studies (14 in low-income to middle-income and high-income countries) with 141 220 participants showing that AF rates increased from 0.34% (<60 years) to 2.73% (≥85 years) and that screen-positive patients are at elevated risk of stroke, with the majority of individuals >65 years having indication of anticoagulation for stroke prevention and >70% having at least one additional stroke risk factor 27. Additionally, some studies postulate that, more than a marker of CV involvement, AF may be an HD itself, being an independent predictor of structural damage and clinical outcomes 28 29.…”
Section: Discussionsupporting
confidence: 79%
“…Why did we not detect more new diagnoses of atrial fibrillation with our extensive and sensitive screening protocol? One reason might be the younger age of the screened patients because the detection rate is dependent on the age of the population 22. Also, the baseline prevalence of atrial fibrillation in the participating centres (10.1%) was higher than in the Rotterdam study (8.1%) and the SAFE study (6.9-7.9%), and much higher than the prevalence reported in a systematic review (4.4%) 2923.…”
Section: Discussionmentioning
confidence: 70%
“…2 3 Screening people ≥65 years in Western countries, with a single screen, is likely to yield 1.44% with new AF. 4 In Japan, screening is likely to identify a lower incidence of AF; however, those identified have a high relative risk of stroke (1.61; 95% CI 0.50 to 5.16) and all-cause mortality (1.71; 95% CI 1.20 to 2.43). 5 International guidelines recommend opportunistic screening for AF in the clinic by pulse palpation in people aged ≥65 years to reduce AF-related strokes.…”
Section: Introductionmentioning
confidence: 99%